A catalogue of the Trichobranchinae (Polychaeta: Terebellidae) of the world - Garraffoni, A. R.s.; Lana, P. C.; Hutchings, P. (Zootaxa, 2005)
A world catalogue of the subfamily Trichobranchinae (Polychaeta: Terebellidae) is provided. Four genera and 58 species are listed, with references to original descriptions, location of types, type locality, and subsequent taxonomic and applied literature.